A respeito dos mortos: remanescentes humanos do Max e suas implicações éticas - Almeida, Thaís Vaz Sampaio de (2018)
Human bone remnants have always aroused a great deal of interest from the academic community and the community at large, above all by the possibility of access to the information inherent to the already extinct populations. Such information brings great enrichment to several areas of knowledge, especially Archeology, since they allow the systematic study of biological, social and cultural factors, among other aspects of these human groups. However, for the most part, this type of vestige is still regarded as a mere object in the service of science. This dissertation seeks to explore this theme, presenting ethical reflections in the proceeding with osteological collections of archaeological origin and brings our attention to the proposed case study: the collection of burials from the Museu de Arqueologia de Xingó, Canindé de São Francisco, SE. In addition to the ethical analysis that permeates the treatment of these traces, we propose a new approach for a sample of this collection, composed of 88 individuals buried that were under surveillance of the Bioarchaeology Laboratory of the Federal University of Sergipe, in Laranjeiras, always seeking to arouse respect for the individuals worked and guided by the notions of conservation and documentation inherent in the area of Museology, the work throws new glances for the conditions of these collections and proposes an interdisciplinarity between this and Archeology. Such interaction will bring great benefits in respect to the memory of human groups, while it will contribute to the sedimentation of reflections about the notions of belonging to these individuals, contributing to the legal delineations of the theme.